2023
DOI: 10.3390/ph16010110
|View full text |Cite
|
Sign up to set email alerts
|

Three Members of Transmembrane-4-Superfamily, TM4SF1, TM4SF4, and TM4SF5, as Emerging Anticancer Molecular Targets against Cancer Phenotypes and Chemoresistance

Abstract: There are six members of the transmembrane 4 superfamily (TM4SF) that have similar topology and sequence homology. Physiologically, they regulate tissue differentiation, signal transduction pathways, cellular activation, proliferation, motility, adhesion, and angiogenesis. Accumulating evidence has demonstrated, among six TM4SF members, the regulatory roles of transmembrane 4 L6 domain family members, particularly TM4SF1, TM4SF4, and TM4SF5, in cancer angiogenesis, progression, and chemoresistance. Hence, targ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 141 publications
0
4
0
Order By: Relevance
“…Previous studies have revealed the underlying mechanism by which TM4SFs are involved in the malignant progression of cancers [5,36]. To further investigate the underlying mechanism responsible for TM4SF family member regulation, we performed gene enrichment analysis of the core genes (protein interactions, co-expressed genes) potentially correlated with TM4SF function.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have revealed the underlying mechanism by which TM4SFs are involved in the malignant progression of cancers [5,36]. To further investigate the underlying mechanism responsible for TM4SF family member regulation, we performed gene enrichment analysis of the core genes (protein interactions, co-expressed genes) potentially correlated with TM4SF function.…”
Section: Discussionmentioning
confidence: 99%
“…The overexpression of TM4SF5, a protein, is a crucial factor in encouraging the proliferation of tumor cells and is consistently found in hepatocarcinoma patients, contributing to hightened expression of TM4SF5 connected to VEGF level and angiogenesis [217]. During TM4SF5-induced multilayer growth, TM4SF5 activates FAK by increasing phosphorylation at Tyr577 (pY577FAK) and enhances the expression and stability of p27Kip1 in the cytosol.…”
Section: Chalconesmentioning
confidence: 99%
“…Rsu1 interacts indirectly with integrin beta-1 via the PINCH/ILK complex, ultimately inhibiting NF-κB. Tm4sf1 interacts constitutively with integrin beta-1 (Shih et al, 2009) and can promote AKT phosphorylation (Rahim et al, 2023).…”
Section: Integrated Analysis Identifies a Subset Of Genes Related To ...mentioning
confidence: 99%